Coronil, a Tri-Herbal Formulation, Attenuates Spike-Protein-Mediated SARS-CoV-2 Viral Entry into Human Alveolar Epithelial Cells and Pro-Inflammatory Cytokines Production by Inhibiting Spike Protein-ACE-2 Interaction - Balkrishna A (Dove Medical Press, 2021)
Acharya Balkrishna,1,2 Swati Haldar,1 Hoshiyar Singh,1 Partha Roy,3 Anurag Varshney1,2 1Drug Discovery and Development Division, Patanjali Research Institute, Haridwar, 249405, Uttarakhand, India; 2Department of Allied and Applied Sciences, University of Patanjali, Haridwar, 249405, Uttarakhand, India; 3Molecular Endocrinology Laboratory, Department of Biotechnology, Indian Institute of Technology Roorkee, Roorkee, 247667, Uttarakhand, IndiaCorrespondence: Anurag VarshneyDrug Discovery and Development Division, Patanjali Research Institute, Roorkee-Haridwar Road, Haridwar, 249405, Uttarakhand, IndiaTel +91-1334-244107, Ext.: 7458Fax +91-1334-244805Email anurag@prft.co.inPurpose: Coronil is a tri-herbal formulation containing extracts from Withania somnifera, Tinospora cordifolia, and Ocimum sanctum. Recently, it was shown that Coronil rescued humanized zebrafish from SARS-CoV-2 induced pathologies. Based on reported computational studies on the phytochemicals present in Coronil, it could be a potential inhibitor of SARS-CoV-2 entry into the host cell and associated cytokines’ production.Methods: Through an ELISA-based biochemical assay, effects of Coronil on interaction between ACE-2 and different mutants of viral spike (S) protein, crucial for viral invasion of host cell, were evaluated. Additionally, using recombinant pseudoviruses having SARS-CoV-2 spike (S) protein in their envelopes and firefly luciferase reporter in their genomes, effects of Coronil on virus entry into human alveolar epithelial cells were evaluated through luciferase assay. UHPLC profiled Coronil also modulated S-protein mediated production of pro-inflammatory cytokines in A549 cells, like interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α), as evaluated through RT-qPCR and ELISA.Results: Coronil effectively inhibited the interaction of ACE-2 not only with the wild-type S protein (SWT) but also with its currently prevalent and more infectious variant (SD614G) and another mutant (SW436R) with significantly higher affinity toward ACE-2. Treatment with Coronil significantly reduced the increased levels of IL-6, IL-1β, and TNF-α in A549 cells incubated with different S-protein variants in a dose-dependent manner. Likewise, it also prevented the SARS-CoV-2 S-protein pseudotyped vesicular stomatitis virus (VSVppSARS-2S) mediated cytokine response in these cells by reducing entry of pseudoviruses into host cells.Conclusion: Coronil prevented SARS-CoV-2 S-protein mediated viral entry into A549 cells by inhibiting spike protein-ACE-2 interactions. SARS-CoV-2 S protein induced inflammatory cytokine response in these cells was also moderated by Coronil.Keywords: Coronil, SARS-CoV-2, pseudovirus, spike protein, ACE-2, pro-inflammatory cytokines